2023
DOI: 10.1021/acsanm.3c00509
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal Therapy with Ag Nanoparticles in Mesoporous Polydopamine for Enhanced Antibacterial Activity

Abstract: Photothermal therapy (PTT) is a promising method to kill pathogenic bacteria. However, using single-modal PTT, it is easy to cause tissue damage because of the overtemperature. Hence, it is necessary to combine PTT with other antibacterial strategies. In this study, we employed silver nanoparticles (Ag NPs) and mesoporous polydopamine (MPDA) nanoparticles to establish a multimodal antibacterial platform (MPDA@Ag). MPDA nanoparticles not only served as a photothermal transduction agent to convert light-energy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…The reduction rate significantly ( p < 0.01) ascended in the Van/PCN+L group, meaning that Van/PCN+L had the best inhibitory effect on the generation of extracellular polysaccharides. Previous studies have reported that extracellular polysaccharides were vital for forming the 3D structure of bacterial biofilm, for polysaccharides served as essential scaffold and mediated microcolony formation in biofilm. , Therefore, the reduction effect of Van/PCN+L on extracellular polysaccharides suggested that the antibacterial nanoplatform possessed the ability to destruct biofilm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction rate significantly ( p < 0.01) ascended in the Van/PCN+L group, meaning that Van/PCN+L had the best inhibitory effect on the generation of extracellular polysaccharides. Previous studies have reported that extracellular polysaccharides were vital for forming the 3D structure of bacterial biofilm, for polysaccharides served as essential scaffold and mediated microcolony formation in biofilm. , Therefore, the reduction effect of Van/PCN+L on extracellular polysaccharides suggested that the antibacterial nanoplatform possessed the ability to destruct biofilm.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that extracellular polysaccharides were vital for forming the 3D structure of bacterial biofilm, 46 for polysaccharides served as essential scaffold and mediated microcolony formation in biofilm. 47,48 Therefore, the reduction effect of Van/PCN+L on extracellular polysaccharides suggested that the antibacterial nanoplatform possessed the ability to destruct biofilm. In addition, CLSM was introduced to investigate the influence of Van/PCN on S. aureus biofilm.…”
Section: The Membranementioning
confidence: 99%
“…After treatments, the obtained bacterial suspensions were centrifuged, washed, fixed, and dehydrated in sequence according to the method described in the literature. 45 Finally, we used SEM to observe the change in bacterial morphology.…”
Section: Inhibition Effects On Biofilmmentioning
confidence: 99%
“…Thus, inorganic materials have gradually become the majority of the antibacterial additives in wood coatings . Nano silver (nano Ag) and nano copper (nano Cu) are the typical antibacterial agents and are widely used in the wood antibacterial domain, by combining with the virtues of inorganic materials and nanomaterials. , The antibacterial activity is attributed to the interaction of nanoparticles and released ions with bacterial cells. In-situ growth of silver particles on the wood surface by the silver mirror reaction could endow the antimicrobial rate of 99.9% .…”
Section: Introductionmentioning
confidence: 99%